Effect of administering kefir on the changes in fecal microbiota and symptoms of inflammatory bowel disease: A randomized controlled trial - İlkay Yılmaz and M. Enver Dolar and Haydar Özpınar (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Kefir is a kind of fermented probiotic dairy product. The objective of the present study was to investigate the effects of kefir consumption on the fecal microflora and symptoms of patients with inflammatory bowel disease (IBD). Materials and Methods: Kefir was serially diluted and inoculated into de Man, Rogosa, and Sharpe agar and incubated at 37°C for 48 to 72 h under anaerobic conditions. This was a single-center, prospective, open-label randomized controlled trial. Forty-five patients with IBD were classified into two groups: 25 for treatment and 20 for control. A 400 mL/day kefir was administered to the patients for 4 weeks day and night. Their stool Lactobacillus, Lactobacillus kefiri, content was quantitated by real-time quantitative polymerase chain reaction before and after consumption. Abdominal pain, bloating, stool frequency, stool consistency, and feeling good scores were recorded in diaries daily by the patients. Results: A 5×107 CFU/mL count of lactic acid bacteria colony forming units was found in a kefir sample as the total average count. Lactobacillus bacterial load of feces of all subjects in the treatment group was between 104 and 109 CFU/g, and the first and last measurements were statistically significant (p=0.001 in ulcerative colitis and p=0.005 in Crohn’s disease (CD)). The L. kefiri bacterial load in the stool of 17 subjects was measured as between 104 and 106 CFU/g. For patients with CD, there was a significant decrease in erythrocyte sedimentation rate and C-reactive protein, whereas hemoglobin increased, and for the last 2 weeks, bloating scores were significantly reduced (p=0.012), and feeling good scores increased (p=0.032). Conclusion: According to our data, kefir consumption may modulate gut microbiota, and regular consumption of kefir may improve the patient’s quality of life in the short term. Cite this article as: Yılmaz İ, Dolar ME, Özpınar H. Effect of administering kefir on the changes in fecal microbiota and symptoms of inflammatory bowel disease: A randomized controlled trial. Turk J Gastroenterol 2019; 30(3): 242-53.